Juan Montaño Escobar, el jazzman de Black Lives Matter, y su son de los 8 minutos 46 segundos (De La Escena Contemporánea) - Handelsman, Michael (2021)
This essay analyses the Ecuadorian Juan Montaño Escobar’s literary response to the Black Lives Movement and the tragic death of George F. Floyd, Jr. on May 25, 2020. More than a protest or denouncement, Montaño Escobar presents a declaration of collective appropriation of those 8 minutes 46 seconds in order to reclaim them as an act of (re)existence and (re) signification precisely because Black Lives Matter and because the movement transcends its time and place as it highlights the systemic racism that defines the history of the Americas.